The Effect Value Orıentatıon, Ecologıcal Knowledge, Ecologıcal Affect, Internal Locus of Controlon Green Purchase Intentıon - Yunita Ramadhani Ratnaningsih DS (APMBA (Asia Pacific Management and Business Application), 2017)
Environmental issue such as global warming become highlight issue in the world. Some environmental issue pointed out as the effect of consumer behavioural which ignored the effect of purchasing to the environmental conservation. For this time environmental issue becoming the important factor for consumer in considering product choosing, even in choosing diapers. This study aims to examine the influence of value orientations on ecological knowledge and ecological affect. This research also aims to investigate the influence of ecological knowledge on ecological affect, also to investigate the influence of ecological knowledge, ecological affect, internal locus of control on green purchase intention. Sampling method is nonprobability sampling with purposive sampling. Data were collected using a questionnaire survey. The  sample in this study consisted of 229 women aged over 17 years old and who have children aged 0 to 24 months in Yogyakarta. The study was based on confirmatory model. Structural equation modeling (SEM) by using AMOS  statistical  program  used  to  test  validity  and  reliability  of  the  instrument,  the goodness of fit model and the relationship hypothesized in the theoretical model proposed. Findings from structural models have proved nearly all the hypothesized relationships. This study reveals that value orientations has a positive effect on ecological knowledge but the effect of value orientations on ecological affect is not supported. Ecological knowledge has a positive effect on ecological affect. Ecological knowledge and internal locus of control has a positive effect on green purchase intention, but the effect of ecological affect on green purchase intentions is not supported.